A Professional Exam as a Resource for Improving the Readiness of a Future Teacher-Psychologist to Support the Educational Process at School - Egorova, M.A.; Lobanova, A.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
An important problem of modern psychological and pedagogical education is the assessment of the readiness of university graduates to carry out the basic professional function of supporting the educational process in educational organizations of different levels. The aim of the article is to study the potential of the demonstration professional examination not only as a resource for identifying the level of professional competencies of students and determining the "zone of nearest development" of these competencies, but also as a resource for improving the readiness of future teacher-psychologists to support the educational process at school. The content and organizational characteristics of the training direction "psychology-pedagogical education" are described, the methodology of which is based on the provisions of the scientific school of cultural-historical psychology, system-activity and competence approaches to the formation of educational results of students. The directions and necessary conditions for improving the developing educational environment of the university are substantiated, which is a resource for increasing the professional readiness of students to support the educational process at school. The analysis of modern researches of effectiveness of professional examination, introduced in the Higher Education Institutions of the Russian Federation is presented. Важной проблемой современного психолого-педагогического образования становится оценка готовности выпускников вуза к осуществлению базовой профессиональной функции по сопровождению образовательного процесса в образовательных организациях различного уровня. Цель статьи заключается в изучении потенциала демонстрационного профессионального экзамена не только как ресурса для выявления уровня сформированности профессиональных компетенций у обучающихся и определения «зоны ближайшего развития» данных компетенций, но и как ресурса повышения готовности будущих педагогов-психологов к сопровождению образовательного процесса в школе. Описаны содержательные и организационные характеристики направления подготовки «Психолого-педагогическое образование», методология которого основана на положениях научной школы культурно-исторической психологии, системно-деятельностном и компетентностном подходах к формированию образовательных результатов обучающихся. Обоснованы направления и необходимые условия совершенствования развивающей образовательной среды вуза, что является ресурсом повышения профессиональной готовности обучающихся к сопровождению образовательного процесса в школе. Представлен анализ современных исследований эффективности профессионального экзамена, внедряемого в вузах Российской Федерации.